The Feasibility Study of Autism Instructional Video based on “Curriculum 2013” For Special Education Teacher - Mohammad Efendi (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2017)
The purpose of this study was to describe it empirically validity level of autistic instructional video based on the curriculum of 2013, feasible and relevant to the needs of the school in order to develop the potential of learners with autism levels of primary and secondary schools. For that, there are several stages of development procedures, among others: the preparation phase, the video production phase and the evaluation phase. Conclusion the analysis shows that the quality of video media-based learning model autistic children based on curriculum 2013 is categorized as very feasible, and can be used as a medium to improve the performance of special teachers in teaching children with autism in Special School. Therefore, it is recommended to teachers or prospective teachers for learners with autism to adapt patterns of learning and enrichment references presented in the instructional video.tujuan penelitian ini adalah mendeskripsikannya secara empiris tingkat kelayakan video model pembelajaran autis berbasis pada kurikulum 2013, yang fisibel dan relevan dengan kebutuhan sekolah dalam rangka mengembangkan potensi peserta didik autis jenjang sekolah dasar dan lanjutan. Untuk itu, ada beberapa tahapan prosedur pengembangannya, antara lain: tahap persiapan, tahap produksi, dan tahap evaluasi. Kesimpulan hasil analisis menunjukkan bahwa kualitas media video model pembelajaran anak autis berbasis Kurikulum 2013 dikategorikan sangat layak, serta dapat digunakan sebagai media untuk meningkatkan performa guru pendidikan khusus dalam membelajarkan anak autis di Sekolah Luar Biasa. Disarankan kepada para guru atau calon pendidik autis untuk mengadopsi pola pembelajaran dan referensi pengayaan yang disajikan dalam video pembelajaran tersebut.